2017
DOI: 10.1142/s0218271817501759
|View full text |Cite
|
Sign up to set email alerts
|

Exponential nonlinear electrodynamics and backreaction effects on holographic superconductor in the Lifshitz black hole background

Abstract: We analytically describe the properties of the s-wave holographic superconductor with the Exponential nonlinear electrodynamics in the Lifshitz black hole background in four-dimensions. Employing an assumption the scalar and gauge fields backreact on the background geometry, we calculate the critical temperature as well as the condensation operator. Based on Sturm-Liouville method, we show that the critical temperature decreases with increasing exponential nonlinear electrodynamics and Lifshitz dynamical expon… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
11
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 63 publications
0
11
0
Order By: Relevance
“…Much research was carried out in Lifshitz scaling by using the holographic approach (see e.g. [59][60][61][62]). However, all the previous work about the effects of Lifshitz scaling on holographic p-wave superconductor was done by considering a SU(2) Yang-Mills gauge field in the bulk in the presence of Maxwell electrodynamics [56,59].…”
Section: Introductionmentioning
confidence: 99%
“…Much research was carried out in Lifshitz scaling by using the holographic approach (see e.g. [59][60][61][62]). However, all the previous work about the effects of Lifshitz scaling on holographic p-wave superconductor was done by considering a SU(2) Yang-Mills gauge field in the bulk in the presence of Maxwell electrodynamics [56,59].…”
Section: Introductionmentioning
confidence: 99%
“…This holographic model undergoes a phase transition from a black hole with no hair to a black hole with scalar hair at low temperatures [8,9]. There exist several studies on holographic superconductors to describe their different aspects [10][11][12][13][14][15][16][17][18][19]. One of the most interesting phenomena in superconductor research is the second order phase transitions in Abelian-Higgs models [9].…”
Section: Introductionmentioning
confidence: 99%
“…It is interesting to investigate the effect of nonlinear electrodynamic models on holographic systems including holographic superconductors [25][26][27][28][29][30][31][32][33][34][35][36][37][38][39][40][41][42][43][44]. Nonlinear models carry more information than the usual Maxwell case and * Electronic address: mkzangeneh@scu.ac.ir † Electronic address: asheykhi@shirazu.ac.ir also are considered as a possible way for avoiding the singularity of the point-like charged particle at the origin [45][46][47][48][49].…”
Section: Introductionmentioning
confidence: 99%
“…The oldest nonlinear electrodynamic model is Born-Infeld (BI) model. There are also two BI-like nonlinear electrodynamics namely logarithmic [33,50,51] and exponential [40,52,53] electrodynamics. It has been found that the exponential electrodynamics has stronger effect on the condensation than other models [54].…”
Section: Introductionmentioning
confidence: 99%